New developments in the management of Waldenström macroglobulinemia - Abeykoon, Jithma P (Cancer Manag Res, 2017)
Waldenström macroglobulinemia (WM) is a rare, immunoglobulin M -associated lymphoplasmacytic lymphoma. With the recent discoveries of CXCR warts, hypogammaglobulinemia, infections, and myelokathexis (WHIM) and MYD88 mutations, our understanding of the biology of WM has expanded substantially. While WM still remains incurable, the field is rapidly evolving, and a number of promising agents with significant activity in this malignancy are being evaluated currently. In this review, we discuss the new developments that have occurred in WM over the past 15 years, with a focus on the role of ibrutinib, an oral Bruton’s tyrosine kinase inhibitor that has recently been approved for WM in the United States, Europe, and Canada.